Matriks Circulant Kompleks Bentuk Khusus 3 × 3 Berpangkat Bilangan Bulat - Dewinta Mamula; Novianita Achmad; Resmawan Resmawan (Jurnal Matematika Integratif, 2021)
This article identifies the general form of matrix power and trace of an integer power of Special Form of the 3 × 3 Complex Circulant matrix. The research begins to determine the general form of an integer power of Special Form of the 3 × 3 Complex Circulant matrix, followed by determining the general form trace of an integer power of Special Form of the 3 × 3 Complex Circulant matrix. The proof is done by using mathematical induction. The final result of this article is to obtain the general form of the matrix A^n and tr(A^n) for n integers in special form of the 3 × 3 complex Circulant matrix.